The Use of Multifunctional Identification Cards in the Education System of the Republic of Belarus - A. N. Kurbatski; Yu. I. Varatnitski; L. P. Kochyn; A. V. Reshetniak; V. I. Dravitsa (Цифровая трансформация)
The article discusses the experience of introducing and using multifunctional identification cards in the education system of the Republic of Belarus. The main advantages of using radio frequency identification technologies are considered. Electronic identification cards have been introduced in the national education system: student cards, employee IDs, student cards. Due to the observance of the principles of continuity of technical solutions in the process of project evolution, solutions are successfully functioning that allow the use of smart cards in functional applications (access control systems in university buildings and dormitories; reader service systems in university libraries, systems for granting benefits to document owners in the provision of various services on the territory of the university). Along with the introduction of multifunctional identification cards, the BSU has created an infrastructure for the use of new electronic documents on the Mifare Plus platform.